L’émergence des émotions dans les sciences psychologiques - Bernard Rimé (L'Atelier du CRH)
Psychological sciences have preceded the other disciplines in the study of emotions. Since the late nineteenth century, a marginal but continuous interest for that matter was manifested. The article reviews the various streams of research that contributed to establish a shared culture among scholars involved in international exchanges in this disciplinary field. These currents are three in number. The oldest one is the biological approach. Inspired by evolutional theory, it views emotions as adaptive biological systems resulting from the history of species. The physiological approach to emotion centered on the examination of bodily changes in emotion constituted a second major research stream that progressively evolved toward the current neuropsychological study of emotions. Finally, much later in time, a cognitive perspective later addressed all the mental processes involved, with a particular accent upon the role played by cognitive processes in triggering emotions.